The Influence Of Health Promotion Aware Of Audio Visual With Demonstration On Adolescent Behavior As Early Detection Of Breast Cancer - Nur Rohmah (An-Najat, 2023)
Background: Lack of information from various media, both print, electronic and cyber media about cancer in efforts to prevent and control breast cancer is still minimal and has not become a top priority for health problems among the public. Many people of productive age are affected by breast cancer, this has made the Indonesian government provide health promotion education about BSE (breast self-examination) to the public, especially teenagers. BSE (Breast Self-Examination) or breast self-examination is a procedure that a woman can perform to physically and visually examine her breasts and armpit area to see changes (Stanford Childern's Health, 2019). Keyword : Background: Lack of information from various media, both print, electronic and cyber media about cancer in efforts to prevent and control breast cancer is still minimal and has not become a top priority for health problems among the public. Many people of productive age are affected by breast cancer, this has made the Indonesian government provide health promotion education about BSE (breast self-examination) to the public, especially teenagers. BSE (Breast Self-Examination) or breast self-examination is a procedure that a woman can perform to physically and visually examine her breasts and armpit area to see changes (Stanford Childern's Health, 2019).